ANALYSIS OF STUDENTS’ MATHEMATICAL SELF-REGULATED LEARNING DURING COVID-19 PANDEMIC - Nazla Nurul Aulia Panggabean; Turmudi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
At the beginning of 2020, the world was horrendous for the COVID-19 virus pandemic that paralyzed all activities, including learning activities at school, which were changed into online learning from home. The purpose of this paper is to provide a description of students' self-regulated learning in Mathematics learning during the Covid-19 pandemic. The research subjects were junior high school students in North Sumatra. The research used qualitative research with descriptive research type. The method used was a survey method through a questionnaire. The research results indicate that students' self-regulated learning in Mathematics learning during the Covid-19 pandemic was in the sufficient category. It can be seen from the results of the questionnaire that students tend to be passive during online learning, tend to be one-way learning focus, which was only teachers to students, tend to work together in doing assignments, and the daily tests given to students look similar.